Post-Lee Kuan Yew World : Is His Strategic Vision Still Relevant? - Han, Fook Kwang (2019)
Singapore’s founding prime minister Lee Kuan Yew shaped the country’s foreign policy since its independence in 1965. But the world has changed much with the shifting geopolitical balance of power and disruptions caused by digital technology. Are Lee’s thinking and strategic vision still relevant in this new world?